백합나무 열처리재의 물리 및 역학적 특성 - 김광모; 박정환; 박병수; 손동원; 박주생; 김운섭; 김병남; 심상로; Kim, Kwang-Mo; Park, Jung-Hwan; Park, Byoung-Soo; Son, Dong-Won; et al. (목재공학, 2010)
Recently, yellow poplar (Liriodendron tulipifera L.) is getting attention in Korea due to the fast growing and high yield and quality of lumber. But, it is thought that the color difference between heartwood and sapwood may restrict the practical use of it. This study was aimed to enhance the value of yellow poplar lumber by the color control using high temperature heat-treatment, which had been tried for domestic cedar (Kim et al., 2009). The material properties including surface color of yellow poplar lumber were evaluated according to heat treatment conditions. The difference of color between sapwood and heartwood could be reduced by heat treatment at a temperature about $200^{°}C$. Long heating time was more effective in reducing the difference. The Equilibrium Moisture Content (EMC) of heat-treated wood was as low as 50 percent of the control. The result obviously indicates that heat-treated wood is more dimensionally stable in the change of moisture condition. The durability against wood rotting fungi also increased by the heat-treated, but it was not so effective as the case of cedar. The changes of mechanical properties of heat-treated yellow poplar were very similar to that of heat-treated cedar. In order to develop new use of heat-treated yellow poplar, the changes of mechanical properties should be considered. There were no significant changes in microscopic structure which may cause changes in mechanical properties. Further study of heat-treated wood is needed to scrutinize the causes of changes of material properties. 본 연구에서는 최근 새로운 활엽수 조림수종으로써 주목받고 있는 백합나무 제재목의 재질개선을 통한 부가가치 향상을 모색하고자 하였다. 이를 위해 이전 연구에서 삼나무의 재질개선 방법으로써 적용가능성이 확인된 $200^{°}C$ 내외의 고온 열처리방법을 적용하였으며, 백합나무 재색제어에 적합한 적정 열처리 조건 구명 및 열처리에 따른 재질변화 평가를 수행하였다. $200^{°}C$의 열처리 조건에서 백합나무 심 변재 사이의 재색차이가 줄어드는 경향을 확인하였으며, 이러한 경향은 처리시간이 증가함에 따라 더 크게 나타났다. 열처리재의 평형함수율이 무처리재에 비해 50% 정도 낮아 목재의 사용과정에서 나타나는 수분에 의한 성능저하를 예방할 수 있을 것으로 기대되었으나, 백합나무의 친환경 방부처리 기술로써 열처리의 적용 가능성은 삼나무에 비해 낮게 나타났다. 열처리재의 역학성능 변화는 삼나무와 거의 유사한 경향을 보였으며, 향후 백합나무의 용도를 개발하는데 있어서 이러한 물성 변화가 고려되어야 할 것이다. 열처리에 의한 물성변화의 원인을 규명하기 위한 미세구조 관찰 결과 에서는 특별한 변화를 확인할 수 없었으며, 추후 물성변화의 원인규명을 위한 추가적인 연구가 요구되었다.